مهارات الكتابة الأكاديمية والنشر العلمي: مقاربة تحليلية تطبيقية - Alnaied, علي إبراهيم النايض; عصام بشير البشري (Surman Journal of Science and Technology, 2025)
Publishing research findings is an integral part of a researcher’s professional life. However, writing is not every researcher’s preferred activity, and publishing a research paper can be a demanding and time-consuming process. Fortunately, many obstacles along the writing and publishing path can be avoided by following certain simple guidelines and best practices. The main objective of this paper is to present a synthesis of existing guidelines in the literature on structuring and writing scientific papers. The paper outlines the process of publishing research papers and highlights the importance of scientific research, aiming to enhance knowledge and provide a comprehensive understanding of research methodology for researchers at all levels. Its objectives include clarifying key research concepts, identifying critical steps in the research process, and covering essential elements such as problem identification, literature review, formulation of questions and hypotheses, research design, and dissemination of results. The paper seeks to provide early-stage researchers with a useful introduction to fundamental research issues. Finally, this paper serves as a fundamental guide that equips researchers with the knowledge and tools needed to navigate the complexities of research methodology, emphasizing the importance of adopting a rigorous and ethical approach.